2022
DOI: 10.1111/sode.12638
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial risk taking and interpersonal regret in children: An individual differences study

Abstract: The relations between prosocial risk taking (taking a risk to benefit another person; PSRT) and interpersonal regret (regret that one's choices have caused a poor outcome for another person) were examined in 192 children aged 7-9.PSRT was measured by children's choices within a gambling task in which one choice guaranteed participants a good prize whereas the other involved risking this prize to help a peer also win a good prize. Interpersonal regret was assessed within the same task by examining children's ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
1
0
1
Order By: Relevance
“…In line with findings on counterfactual thinking discussed above, a number of studies suggest that children do not show evidence of experiencing regret until around the age of 6 (Guerini et al, 2020;McCormack et al, 2016;O'Connor et al, 2012;Van Duijvenvoorde et al, 2014;Weisberg & Beck, 2010). Moreover, research has found that children who experience regret make better choices in the future (McCormack et al, 2019;O'Connor et al, 2014O'Connor et al, , 2015, and feel bad if their choice led to a negative outcome for another child (Corbett et al, 2021;Corbett et al, 2022;Uprichard & McCormack, 2018). This body of work shows that counterfactual thinking about their own choices has consequences for how children feel and act (see McCormack et al, 2020 for review).…”
Section: Counterfactual Thinking and Social Cognition In Childhoodmentioning
confidence: 52%
“…In line with findings on counterfactual thinking discussed above, a number of studies suggest that children do not show evidence of experiencing regret until around the age of 6 (Guerini et al, 2020;McCormack et al, 2016;O'Connor et al, 2012;Van Duijvenvoorde et al, 2014;Weisberg & Beck, 2010). Moreover, research has found that children who experience regret make better choices in the future (McCormack et al, 2019;O'Connor et al, 2014O'Connor et al, , 2015, and feel bad if their choice led to a negative outcome for another child (Corbett et al, 2021;Corbett et al, 2022;Uprichard & McCormack, 2018). This body of work shows that counterfactual thinking about their own choices has consequences for how children feel and act (see McCormack et al, 2020 for review).…”
Section: Counterfactual Thinking and Social Cognition In Childhoodmentioning
confidence: 52%
“…Perilaku prososial di sekolah, seperti membantu dan berbagi, berkontribusi pada perkembangan individu yang positif, hubungan teman sebaya, dan iklim kelas (B. Corbett et al, 2023). Perilaku prososial lebih terlihat pada siswa yang lebih tua, perempuan, dan siswa dengan fungsi umum yang lebih tinggi, namun perilaku prososial teman sekelas tidak memengaruhi perilaku prososial individu di kemudian hari (B.…”
Section: Hasil Dan Pembahasanunclassified